CHALLENGES AND OPPORTUNITIES IN ONLINE ASSESSMENT: VOCATIONAL TEACHERS’ PERSPECTIVES ON PEDAGOGICAL TRANSFORM IN DIGITAL ERA - Ida Ayu Candrawati; Ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra (STKIP PGRI Tulungagung, 2025)
This study examines the challenges and opportunities encountered by vocational high school teachers in implementing online assessments and how these experiences facilitate their pedagogical development. The research employed a qualitative phenomenological design, involving six vocational teachers from several disciplines who had administered online exams for a minimum of one academic year. Data were gathered via semi-structured interviews, document analysis, and a focus group discussion. Thematic analysis was employed to identify emerging patterns and meanings within the participants' stories. The results indicate that teachers initially encountered several obstacles, including insufficient technological proficiency, inadequate institutional support, and unequal access to digital resources among students.Notwithstanding these challenges, teachers have shown flexibility and ingenuity by formulating innovative assessment methods, including digital portfolios, performance-based activities, and interactive rubrics. These improvements promoted increased student autonomy and involvement, converting assessment into a learning-focused process rather than a simple evaluation task. Teacher collaboration developed as a vital element in surmounting challenges and maintaining professional development. The study indicates that online assessment functions as both a challenge and a driver of educational transformation. It underscores the necessity for ongoing professional development and institutional backing to improve teachers' digital literacy and reflective practices. The study implies that well-designed and adequately supported online assessments can foster genuine learning and professional rejuvenation in vocational education.